Hubungan Tingkat Pengetahuan dan Sikap Penggunaan Cartridge Respirator terhadap Kadar S-Pma dalam Urine Pekerja Produksi di CPA Tahun 2022: Studi Kasus: PT. TI, Kalimantan Timur - Andi Sujito; Sri Ratna Astuti; Kun Lukito (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2023)
Benzene is well-known as a carcinogen and one of work related disease causes. High level benzene exposure causes nerve and blood forming disruption, One of benzene biomarker is a S-PMA (S-phenylmercapturic acid). The question appear “Is there correlation between knowledge level and attitude obedient of cartridge respirator equipment usage with the S-PMA urine value of production worker”. Purpose of this research is to observe the correlation of knowledge level and attitude obedient e of cartridge respirator equipment usage with the S-PMA urine value of production worker in PT. TI, East Kalimantan. This research methode is an observasional quantitative, time approach “cross sectional” and descriptive data analysis. Total sample is 86 responden from both process and well department. Data collestion using questionaire and seconder data of benzene, S-PMA and passive sampler measurement. Knowledge level and attitude obedient of cartridge respirator equipment usage is appearing good (94,2%). Knowledge level of cartridge respirator equipment usage affect the S-PMA urine value (Pearson correlation r = 0,097). The attitude obedient of cartridge respirator equipment usage affect the S-PMA urine value (Pearson correlation r = 0,195). Knowledge level and attitude obedient of cartridge respirator equipment usage is appearing good. There’s a correlation between knowledge level and attitude obedient of cartridge respirator equipment usage with the S-PMA urine value of production worker. The implementation and supervision of Benzene Management program in parrarel of cartridge and Respirator usage should be continue and must be perfomed well supervision.